From the Idea to Execution: Writing Organization Method for Undergraduate Management Students - Husaini, Rizqi (Papanda Publisher, 2025)
This study explores the organizational strategies used by undergraduate management students in an English for Specific Purposes (ESP) course and examines how English language proficiency influences their academic writing. Effective organization is critical for clear communication in both academic and professional management contexts, yet many students—especially those in ESL/EFL environments—struggle with structuring their ideas due to limited language skills and unfamiliarity with academic conventions. Using a qualitative descriptive approach, the study analyzed students’ written assignments to identify common patterns and evaluate their use of organizational techniques. The findings reveal that students frequently employed three main strategies: chronological order, spatial/classification, and compare and contrast. Many also combined multiple strategies to better align their structure with the content and purpose of their reports. These patterns reflect students’ growing awareness of academic writing expectations and their attempts to improve coherence and clarity in English. The study highlights the importance of integrating writing instruction into management curricula, particularly focusing on teaching flexible, discipline-specific organizational methods. Enhanced support in this area can significantly improve students’ writing performance and better prepare them for future professional roles. Further research could explore how these skills develop over time and compare strategy use across academic disciplines.